A Case Study Investigating the Utilization of ChatGPT in Online Discussions - Lin, Xi; Luterbach, Ken; Gregory, Kristen H.; Sconyers, Sarah E. (Online Learning, 2024)
This study explored the impact of integrating ChatGPT into asynchronous online discussions. The analysis encompassed students’ log data from Canvas and their perspectives on using ChatGPT. Results revealed a significant enhancement in overall discussion participation when ChatGPT is encouraged, emphasizing its potential as a catalyst for constructive conversations and the development of generic skills. Students also acknowledge ChatGPT’s positive influence on critical thinking and knowledge exploration. In summary, integrating ChatGPT not only enhances participation and engagement but also fosters a sense of community, promotes online interaction, and cultivates essential skills. This study concluded by discussing issues associated with using ChatGPT for online discussions and highlighting implications for its appropriate integration into online discussion boards.